Production and Study of Boron and Nitrogen-doped Carbon Nanotubes by Arc Discharge Method Using Dispersive Raman Back-Scattering Spectroscopy - BABANEJAD*, S.A.; MALEKFAR†, R.; ASHRAFI‡, F.; SEID HOSSEINI†, S.M.R. (Asian Journal of Chemistry, 2009)
Raman scattering studies reveal the remarkable structure and the unusual electronic and phonon properties of carbon nanotubes (CNTs). In this study, we directly produced boron and nitrogen doped CNTs by using DC-arc discharge method which normally can be employed for producing CNTs. An experiment was performed without the catalyst and in the presence of Ar gas for producing boron doped CNTs. At the second and third stages and in the presence of Al2O3 and MgO as catalysts and nitrogen, N2 gas were used for producing nitrogen doped CNTs. In general, present investigation revealed that some major changes caused by boron and nitrogen dopants can be observed in the related recorded Raman spectra.